Varied Relationship of Lipid and Lipoprotein Profiles to Liver Fat Content in Phenotypes of Metabolic Associated Fatty Liver Disease - Wu, Tingfeng; Ye, Junzhao; Shao, Congxiang; Li, Fuxi; Lin, Yansong; Ma, Qianqian; Wang, Wei; Feng, Shiting; Zhong, Bihui (Frontiers in Endocrinology, 2021)
Background Progressive overloads of intrahepatic triglycerides are related to metabolic dysregulation of multiple lipid and lipoprotein profiles, but whether similar dose effects are found in each subtype of metabolic associated fatty liver disease (MAFLD) remains unclear. We aimed to characterize the lipid profiles associated with liver fat content (LFC) in MAFLD patients who were overweight, lean/normal weight, or had diabetes. Methods We conducted a cross-sectional study enrolling 1,182 consecutive participants (144 non-MAFLD and 1,038 MAFLD) who underwent MRI proton density fat fraction measurement (MRI-PDFF) from 2011 to 2020. Lipid and apolipoprotein profiles, free fatty acid (FFA), liver and metabolism parameters, and anthropometric measurements were also assessed. Results MAFLD patients with type 2 diabetes or overweight/obesity had a higher proportion of abnormal lipid and lipoprotein profiles than those who were lean/normal weight. The degree of LFC had a positive correlation with total cholesterol, triglyceride, ApoB, and ApoE in patients with overweight/obesity and type 2 diabetes. In those with overweight/obesity, there were dose–response relationships between moderate-to-severe steatosis and total cholesterol, triglyceride, HDL-c, LDL-c, ApoB, ApoE, and Lp(a). A similar trend was observed for triglyceride in those with type 2 diabetes and for HDL-c in patients who were lean/normal weight (all p for trend <0.05). The combined model of relative lipid-related markers performed well in the prediction of moderate-to-severe steatosis (AUC: 0.762 for overweight/obesity; 0.742 for lean/normal weight). Conclusion LFC was associated with lipid profiles, including triglyceride, LDL-c, ApoB, ApoE, and FFA. These relationships were varied by the phenotype of MAFLD according to its diagnostic flow.